1999
DOI: 10.1111/j.1550-7408.1999.tb04597.x
|View full text |Cite
|
Sign up to set email alerts
|

Affinity‐Purification of Concanavalin A‐Binding Ciliary Glycoconjugates of Starved and Feeding Tetrahymena thermophila

Abstract: Development of mating competency in Tetrahymena thermophila requires starvation for at least 70 min in low ionic strength buffer. Pair formation between conjugating cells is blocked at early stages by the lectin Concanavalin A (Con A). To investigate the role of Con A-binding proteins in this induced cellular change and pairing, and to confirm and extend an earlier study from our laboratory, a method was developed for preparation of Con A-binding proteins from ciliary membrane-rich fractions of T. thermophila.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Pursuing pheromone purification and characterization has been more successful in Blepharisma, Dileptus, and Euplotes, because these ciliates secrete and diffuse their pheromones constitutively in biologically detectable concentrations into the extracellular environment, unlike Paramecium and Tetrahymena which apparently retain these molecules bound to the cell surface (Hiwatashi Kitamura, 1985;Kitamura, 1988;Wolfe, 1993;Driscoll & Hufnagel, 1999). In the environment, pheromones have usually been revealed by mating-induction assays in which the formation of mating pairs is induced after suspension of a cell culture with cell-free supernatant of another culture of different mating type.…”
Section: Introductionmentioning
confidence: 99%
“…Pursuing pheromone purification and characterization has been more successful in Blepharisma, Dileptus, and Euplotes, because these ciliates secrete and diffuse their pheromones constitutively in biologically detectable concentrations into the extracellular environment, unlike Paramecium and Tetrahymena which apparently retain these molecules bound to the cell surface (Hiwatashi Kitamura, 1985;Kitamura, 1988;Wolfe, 1993;Driscoll & Hufnagel, 1999). In the environment, pheromones have usually been revealed by mating-induction assays in which the formation of mating pairs is induced after suspension of a cell culture with cell-free supernatant of another culture of different mating type.…”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to label co‐stimulated cells with monovalent TRITC‐ConA and pursue whether or not the streaming can be observed in the absence of cross‐linking. It has been reported that novel ConA receptors are not synthesized in response to mating induction, but rather that co‐stimulation leads to a global redistribution of existing receptors, resulting in their aggregation over the future mating junction at the anterior end of the cell (Driscoll and Hufnagel 1999; Van Bell 1983; Wolfe and Feng 1988). Perhaps these ConA “zippers” represent early patterns of receptor flow as this global reorganization is achieved.…”
mentioning
confidence: 99%